2016
DOI: 10.1128/mcb.00064-16
|View full text |Cite
|
Sign up to set email alerts
|

New Regulatory Roles of Galectin-3 in High-Affinity IgE Receptor Signaling

Abstract: c Aggregation of the high-affinity receptor for IgE (FcRI) in mast cells initiates activation events that lead to degranulation and release of inflammatory mediators. To better understand the signaling pathways and genes involved in mast cell activation, we developed a high-throughput mast cell degranulation assay suitable for RNA interference experiments using lentivirus-based short hairpin RNA (shRNA) delivery. We tested 432 shRNAs specific for 144 selected genes for effects on FcRI-mediated mast cell degran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 79 publications
0
23
0
2
Order By: Relevance
“…Gal-3 is a central regulator of critical processes under the setting of acute and chronic inflammation. Gal-3 is involved in the process of acute inflammatory response including chemoattraction of monocytes/macrophages [19], neutrophil clearance [20], opsonization of apoptotic neutrophils [21], and mast cell degranulation [22]. Through interacting with nucleotide oligomerization domain-like receptor protein 3 (NLRP3), intracellular Gal-3 enhanced the effects of H5N1 infection by promoting host inflammatory responses and regulating interleukin-1 beta (IL-1β) production by macrophages.…”
Section: Gal-3 and Inflammationmentioning
confidence: 99%
“…Gal-3 is a central regulator of critical processes under the setting of acute and chronic inflammation. Gal-3 is involved in the process of acute inflammatory response including chemoattraction of monocytes/macrophages [19], neutrophil clearance [20], opsonization of apoptotic neutrophils [21], and mast cell degranulation [22]. Through interacting with nucleotide oligomerization domain-like receptor protein 3 (NLRP3), intracellular Gal-3 enhanced the effects of H5N1 infection by promoting host inflammatory responses and regulating interleukin-1 beta (IL-1β) production by macrophages.…”
Section: Gal-3 and Inflammationmentioning
confidence: 99%
“…At the cellular level, Gal-3 can be located in the cytoplasm, nucleus, and membranes, and it can also be found extracellularly after being released from cells following different stimuli, like LPS and interferon- γ , in both physiological and pathophysiological conditions [ 18 , 19 ]. Several different functions have been attributed to intracellular Gal-3, including antiapoptotic activity and the regulation of mRNA splicing [ 20 , 21 ], regulation of the Fc ε RI signaling pathway in mast cells [ 22 ], and modulation of the activation of RhoA and MLCK during cell invasion in hepatocellular carcinoma [ 22 , 23 ]. For its part, extracellular Gal-3 (either membrane associated or free) also participates in a wide range of functions, including immunity against pathogens, and in both acute and chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Gal-3 has been shown to be a negative regulator of mast cell degranulation induced by IgE receptor activation (FcERI) 38. In this study, murine mast cells silenced for the Gal-3 gene (Gal-3 KD) showed exacerbated degranulation in comparison to non-silenced cells after IgE stimulation.…”
Section: Discussionmentioning
confidence: 81%